Analisis SWOT Pada Usaha Mikro, Kecil dan Menengah (UMKM) (Study Kasus Pada Mie Gacoan) - Ibanez Nura Adi; Daspar Daspar (BISMA : Business and Management Journal, 2025)
This study aims to analyze the implementation of business strategies in Micro, Small, and Medium Enterprises (MSMEs) with a case study of Mie Gacoan using SWOT analysis. Mie Gacoan is one of the rapidly growing culinary brands in Indonesia, known for its affordable prices and extensive outlet network. This research employs a qualitative descriptive approach with observational methods, where data is collected through direct observation of operational activities, customer service, inventory management, and promotional strategies at Mie Gacoan outlets. The results indicate that Mie Gacoan has strengths in competitive pricing, high sales volume, and strategic locations. However, there are weaknesses such as long queues and inconsistency in service across different branches. Opportunities that can be leveraged include the development of new menu items, collaboration with influencers, and expansion into new areas. On the other hand, the main threats come from intense competition, rising raw material prices, and changing consumer preferences. This SWOT analysis provides a strategic overview for Mie Gacoan to capitalize on its strengths and opportunities while addressing its weaknesses and threats, thereby enhancing competitiveness and maintaining customer loyalty in the competitive culinary industry.